2019
DOI: 10.1016/j.imlet.2019.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Impact of B cell/lymphoid stromal cell crosstalk in B-cell physiology and malignancy

Abstract: Highlights-Lymphoid stromal cells form a heterogeneous and plastic cell compartment -Follicular and extrafollicular stromal cells contribute to normal B-cell activation -FL-CAFs exhibit specific phenotypic and transcriptomic features -FL B cells and their immune microenvironment trigger FL-CAF differentiation -FL-CAFs support directly malignant B-cell growth and organize tumor cell niche Abstract Stromal cells have been considered for a long time essentially as a structural component organizing tissue architec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 82 publications
1
14
0
Order By: Relevance
“…As an example, we demonstrated that the introduction of n -glycosylation acceptor sites harboring unusual high-mannose oligosaccharides in FL BCR triggers the interaction of malignant B cells with DC-SIGN-expressing tumor-infiltrating macrophages resulting in BCR-dependent FL B cell activation [ 11 ]. In addition, malignant FL B cells display a substantial dependency on their microenvironment organized as specific supportive cell niches providing survival and proliferation signals (reviewed in [ 12 , 13 ]). Composition and spatial organization of the FL niches have a huge impact on patient prognosis, as initially described by Dave et al [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…As an example, we demonstrated that the introduction of n -glycosylation acceptor sites harboring unusual high-mannose oligosaccharides in FL BCR triggers the interaction of malignant B cells with DC-SIGN-expressing tumor-infiltrating macrophages resulting in BCR-dependent FL B cell activation [ 11 ]. In addition, malignant FL B cells display a substantial dependency on their microenvironment organized as specific supportive cell niches providing survival and proliferation signals (reviewed in [ 12 , 13 ]). Composition and spatial organization of the FL niches have a huge impact on patient prognosis, as initially described by Dave et al [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Under normal conditions, a clear inter-relationship exists between B cells and the fibro-reticular network, (FRN) of secondary lymphoid organs. This is also observed in pathological conditions ( 11 ), particularly in lymphoma and during the formation of tertiary lymphoid structures in the context of inflammation ( 12 ). In the case of FL, cross talk between tumor cells and cells of the local FRN drives their differentiation into tumor-supporting lymphoid stroma ( 13 ).…”
Section: Introductionmentioning
confidence: 77%
“…They organize and regulate immune cell trafficking, differentiation, and migration of T cells through an IL-4/CXCL12 communication axis with T FH , among other signals, and secretion of additional chemokines such as CCL19 and CCL21. FRC also plays a direct role in B malignant cells' activation and survival through BAFF signaling [16][17][18][19].…”
Section: Fl Microenvironment: Friend or Foe?mentioning
confidence: 99%